# Algebra

2x + 1/2 = x/2 + 1/3

Subtract the x/2 from both sides to get
2x + 1/2 - x/2 = + 1/3
Now subtract 1/2 from both sides to get
2x + - x/2 = 1/3 - 1/2
Then combine terms on both sides and solve for x.

Subtract the x/2 from both sides to get 2x + 1/2 - x/2 = + 1/3
Now subtract 1/2 from both sides to get
2x + - x/2 = 1/3 - 1/2. Then combine terms on both sides and solve for x.

1/(4X^-10 y^14)

one over 4x to the neg. 12 y to the 14th

1/(4x^-10 y^14)
The problem in words:
one over 4x to the neg. 12th y to the 14th

1. 👍
2. 👎
3. 👁

## Similar Questions

1. ### math

Match the equation with the step needed to solve it. 1. 2m - 1 = 3m subtract m 2. 2m = 1 + m subtract 2 3. m - 1 = 2 subtract 1 4. 2 + m = 3 subtract 2m 5. -2 + m = 1 add 2 6. 3 = 1 + m add 1

Quinda begins to solve the equation Negative 4.5 x + 3 = 2 minus 8.5 x by adding 8.5x to each side of the equation. Which next step would result in the variable terms and constant terms being on different sides of the equals sign?

3. ### algebra

Which could be a first step in solving the equation 1/4x+1/2=3/4x in an efficient way? Select two answers. A.multiply by 4 on both sides B.multiply by 2x on both sides C.subtract 1/4x from both sides D.add 1/2 to both sides plz

4. ### Pre-calc Solve logarithmic

ln sqrt(x-8)= 5 I would like help to solve this what i did was to take away the square root i squared both sides coming up with (ln sqrt(x-8))^2= (5)^2 ln(x-8)=25 am i alowed to do this with ln in the equation? then i subtract 8

1. ### maths

For the formula Y = AX + B to make X the subject wod it be X = AY – B ?? no ax+b=y subtract b from both sides, then divide both sides by a.

2. ### algebra

What is the first step to solving the equation: 4(x + 4) = 24 Add 4 to both sides, subtract 4 from both sides, or distribute 4 times x + 4?

3. ### Algebra

Which of the following describes a correct method for solving the equation below? -7/2n + 5 = -16 1. add 5 to both sides, then divide both sides by 2/7 2. subtract 5 from both sides, then multiply both sides by -7/2 3. add -5 to

4. ### Algebra

The first step to solve for y in y/3= 6 + x is A) to subtract x from both sides of the equation. B) to subtract y/3 from both sides of the equation. C) to divide each term on both sides of the equation by 3. ******* D) to multiply

1. ### maths

how do i Rearrange the formula Y = 5X + 7 so that X is the subject. and i need to show my method carefully. subtract seven from both sides. divide both sides by five. Y=5x+7 Y-7=5x Y-7/5=x

2. ### algebra

how can i solve the inequality x+9>12 do i subtract -9 from both sides?

3. ### ALGEBRA

Select all the statements that can be used as steps to solve the equation 6[4(2x−1)]=80−8. Subtract 8 from 80. Combine 80 and 6. Multiply 2x and -1 by 4. Subtract 1 from both sides of the equation. Add 4 to both sides of the